Pendampingan Uji Kandungan Karbohidrat Pada Makanan Bagi Calon Guru Sekolah Dasar - Dongoran, Jhonas; Sinaga, Eka Margareta; Br. Ginting, Siska Yolandasari; Situmorang, Desi Ratna Sari; Girsang, Kormeliaty; Panjaitan, Nomita; Sinaga, Ida Hotnauli (PUAN INDONESIA, 2025)
The implementation of the mentoring activity of carbohydrate content testing in food for prospective elementary school teachers as a learning innovation aims to improve teacher skills in learning and can improve the learning outcomes of students in science learning in grade IV of Elementary School 060893 Medan in the 2023/2024 academic year. This activity aims for prospective teachers to be able to integrate learning innovations through carbohydrate testing in food, so that the learning process activities become effective and efficient in accordance with the characteristics of elementary school science learning. The activity method is carried out through several stages of activities including: preparation activities, implementation, and evaluation. The results of the community service program show that science learning outcomes have increased in grade IV at Elementary School 060893 Medan.